(untitled) (Bangladesh Journal of Botany, 2025)
Thirty-eight garlic genotypes were evaluated for their genetic variability attributes during Rabi, 2021-2022. Estimation of phenotypic and genotypic coefficient variation was high for stemphylium blight incidence and clove count per bulb. High heritability along with high genetic advance was observed in plant height, bulb breadth, bulb weight, number of cloves per bulb, bulb, clove length and yield per plot. Bulb yield per plot was positively and significantly associated with plant height, number of leaves per plant, bulb length and bulb breadth. Bulb weight exhibited positive and direct effect on bulb yield followed by total soluble solids, drying percentage and bulb breadth. Cluster analysis grouped the genotypes into distinct clusters, highlighting substantial genetic diversity. Principal component analysis revealed significant variability, with the first five components explaining 75.47% of the total variation. Therefore, selection based on these traits could be effective for higher bulb yield in garlic genotypes. Bangladesh J. Bot. 54(2): 319-324, 2025 (June)